Configuring Windows 8® Exam 70-687 : lab manual - Zacker, Craig (John Wiley & Sons, Inc. HobokenUS, 2014)
Presents lab worksheets which requires the user to answer questions, create screenshots and perform activities relating to topics such as evaluating hardware readiness and capability; installing Windows 8; migrating and configuring user data; installing and configuring desktop applications; configuring Internet Explorer, Hpver-V, IP Settings, network settings, shared resources, file and folder access; security for mobile devices; which are documented on the book companion site provided.